The philanthropic planning companion : the fundraisers' and professional advisors' guide to charitable gift planning - Sagrestano, Brian M., 1969-; Wahlers, Robert E., 1965- (Hoboken, N.J. : Wiley, 2012)
'A donor-centered guide to charitable gift planning for fundraisers and professional advisorsThe Philanthropic Planning Companion compiles and analyzes the latest research on donor/client behavior, discussing the need for segmented approaches to charitable gift planning based upon the values and personal planning objectives of the donor/client. With its many tools, checklists and sample materials, it will serve as your charitable giving guide in your work with your donors/clients. Whether you are building your practice to work with high net worth clients or you are enhancing your fundraising program, this is the book you will keep close at hand. Outlines how an integrated, donor-centered, values-based, philanthropic planning approach can be implemented Explores the latest research focuses on donor behavior For fundraisers and professional advisors alike, The Philanthropic Planning Companion is the one-stop resource you'll keep by your side to help your donors/clients meet their charitable and personal planning objectives'--
Includes bibliographical references (p. 401-405) and index.
Keywords: Fund raising; Nonprofit organizations -- Finance; Charities; Endowments